Political Participation in Elections of the Lower Northern Region Province - Opsin, Sukanyanat; Adivadhanasit, Chamnong; Suyaprom, Surapon (Dhammathas Academic Journal, 2022)
The objectives of this research paper were to study the political participation of the people in the general elections of the lower Northern provinces. This research is a mixed method research. The sample group consisted of 400 samples from the population who voted according to the database of the Department of Provincial Administration. Ministry of Interior as of December 31, 2018 from 4 provinces in the lower Northern provinces, including Nakhon Sawan, Phichit, Kamphaeng Phet and Uthai Thani, totaling 2,199,250 people by random sampling. The research tools were questionnaires, qualitative research. It’s an in-depth interview. With key informants that were specifically selected as qualified 18 experts person.Data were analyzed from questionnaires using a social science research package using statistics. Statistics used in data analysis Contains descriptive statistics. Findings were as follows: Opinions on People’s Political Participation in the General Election of the Lower Northern Provinces The overall results of the analysis of opinions on political participation of the people in the general elections in the lower Northern provinces were of a high average. When considering each aspect, it was found that participation in the form of elections was followed by participation in the form of political parties.